The Role of Early Maladaptive Schemas and Illness Anxiety in Predicting Hypochondriasis in Patients with Recurrent Emergency Department Visits - Derakhshan, Nafiseh; Moradi, Ahmad; Momeni, Fatemeh; Mohammadgholiha , Alireza; Mostafavi , Elham; Zadhasan, Zohreh (Mental Health and Lifestyle Journal, 2025)
This study aimed to examine the predictive role of early maladaptive schema domains and illness anxiety in hypochondriasis among patients with recurrent emergency department visits in Tehran. A correlational descriptive design was employed, and 410 participants were recruited based on the Morgan and Krejcie sample size determination table using convenience sampling. Inclusion criteria were being 18 years or older, Persian literacy, and repeated emergency department attendance, with exclusion of individuals with acute psychosis or severe cognitive impairment. Participants completed the Whiteley Index for hypochondriasis, the Young Schema Questionnaire–Short Form (third edition) for early maladaptive schema domains, and the Illness Anxiety Scale. Data were analyzed using IBM SPSS Statistics version 27. Pearson correlation coefficients were computed to examine the relationships between hypochondriasis and each predictor variable. Multiple linear regression analysis was performed with hypochondriasis as the dependent variable and five schema domains plus illness anxiety as independent variables. Statistical significance was set at p < 0.05. Pearson correlation analysis revealed that hypochondriasis was significantly and positively correlated with all schema domains and illness anxiety (p < .001), with the strongest associations observed for illness anxiety (r = 0.69) and disconnection & rejection (r = 0.61). Multiple regression analysis showed that the model significantly predicted hypochondriasis, F(6, 403) = 108.26, p < .001, explaining 61% of the variance (adjusted R² = 0.60). All predictors were statistically significant, with illness anxiety (β = 0.38) and disconnection & rejection (β = 0.24) being the strongest contributors. Early maladaptive schema domains and illness anxiety significantly predict hypochondriasis in patients with recurrent emergency visits. The findings underscore the importance of assessing and targeting both maladaptive schemas and illness-related fears in interventions designed to reduce unnecessary emergency utilization and improve psychological well-being.